2022
DOI: 10.3390/su14031484
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Sustainability during COVID-19: Last Mile Food Delivery in China

Abstract: The COVID-19 pandemic triggered a strict 100-day lockdown period in Spring of 2020 in China. One of the consequences of the lockdown was the disruption of the food supply chain for the millions of people confined to their homes. The well-established online food delivery service (OFDS) in China were disrupted by pressure to scale up rapidly to resolve the last mile of food delivery. The importance of the OFDS during periods of crises became apparent, as did the realization that uninterrupted food distribution w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…A review of the research into food delivery and sustainable development goals found that consumer behavior studies are still in the early stages (e.g., there was not much use for drone food delivery. As a result, business owners were required to do a significant amount of marketing [44]. The article "Supply Chain Sustainability During COVID-19: Last Mile Food Delivery in China" analyzed factors affecting consumer acceptance for sustainability in business operations [45], specifically, the last mile of online food delivery on the Glovo platform.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the research into food delivery and sustainable development goals found that consumer behavior studies are still in the early stages (e.g., there was not much use for drone food delivery. As a result, business owners were required to do a significant amount of marketing [44]. The article "Supply Chain Sustainability During COVID-19: Last Mile Food Delivery in China" analyzed factors affecting consumer acceptance for sustainability in business operations [45], specifically, the last mile of online food delivery on the Glovo platform.…”
Section: Introductionmentioning
confidence: 99%
“…In the reviewed studies, researchers focused on COVID-19-related risks in addition to discussing the traditional risk dimensions. Perceived risk usually negatively influences consumers’ behavioral intention or attitude; however, fear of COVID-19 [ 13 ] and perceived severity [ 44 ] were found to positively influence consumers’ intention to use food delivery services. This is because researchers viewed the perceived COVID-19-related risks from different perspectives (see Section 3.2.2 ).…”
Section: Resultsmentioning
confidence: 99%
“… Theme 1: technical and utilitarian factors [ 6 , 12 , 13 , 15 , 26 , 35 , 36 , 37 , 42 , 44 , 46 , 48 , 53 , 54 , 55 , 56 , 58 ]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations